Data-Driven Modeling to predict forest fire spread in the Patagonian region in Argentina - Becerra, Lucas (2026)
Fil: Becerra, Lucas. Instituto Balseiro. Universidad Nacional de Cuyo, San Carlos de Bariloche, Río Negro, Argentina